SKRINING IN SILICO SENYAWA AKTIF BENGKOANG (Pachyrrhizus erosus) SEBAGAI ANTITIROSINASE PADA Aspergillus oryzae (STUDI KOMPUTASIONAL DENGAN HOMOLOGY MODELING DAN MOLECULAR DOCKING) - Lukitaningsih, Endang; Wisnusaputra, Aditya; Sudarmanto, B. S. Ari (Majalah Obat Tradisional, 2015)
Bengkoang has been widely used in the cosmetics industry as a whitening agent. Based on research by Lukitaningsih (2009), bengkoang contains 6 active compounds thatÂ  acts as a inhibitors of the Aspergillus oryzae (TyrAo) tyrosinase enzyme. However, the interaction between the active compounds in bengkoang and the enzyme tyrosinase has not been known yet. Interaction between bengkoangs active compounds and TyrAo enzyme can be identified by computational studies (in silico). The interaction is conducted using homology modeling and molecular docking. Homology modeling performed to design a three-dimensional (3D) model of Aspergillus oryzae tyrosinase enzyme (TyrAo) using a template form of known 3D structure of TyrAb enzyme (PDBID: 2Y9X). TyrAo model used as target macromolecules in molecular docking method. Molecular docking method is a method to describe ligand (active compounds) position on the active receptor (TyrAo model). Based on the docking results, it is known that residues interacting on the active site of tyrosinase enzyme were Thr275 and His294 residues. The Thr275 made a hydrogen bonding, while the His294 residue made a hydrophobic interaction on the aromatic ring. Experiments in silico and in vitro have been done; the results exhibited a good correlation of them with R2 value of -0.8366. This correlation indicates that the activity of the active compounds in Bengkoang was similar with the results of them in silico and in vitro studies.